A social cause on Real Time Implementation of Automatic Fall Detector and Location Tracking System Using LSM for elder age peoples - T. Senthil Kumar; S. Sivasankari; A. Sundar Raj (International Journal of Psychosocial Rehabilitation, 2020)
Considering a social cause for elder people may encounter problems if they are living alone with their poor health condition at their old age. In this project, a prototype of elderly fall detection and location tracking system is developed by using the Global Positioning System (GPS), Global System for Mobile communications (GSM), Wi -Fi and Ardino technologies. The proposed system is software equipped with cellular network and Wi-Fi connectivity for sending an emergency alert in multiples ways such as Short Message Services (SMS) and email in case of fall detected. The Coding is written by the use of Python. The location coordinate is extracted from a GPS module and sent together with emergency alerts in the form of Google Map link to caretaker for immediate action. The prototype is tested. It sends emergency SMS and Email via GSM and cloud server respectively, if a fall is detected. Moreover, the proposed system stored the fall event details on cloud server and display on a webpage.